Analysis of Financial Performance of Undervalued Companies in the Manufacturing Sector on the Indonesian Stock Market - Burhan, Mahardika; Hidayat, Rahmat; Jamarang, Satriani; Alifa, Sarah (AFEBI Accounting Review, 2024)
This research aims to explore how to utilize the value investing approach for investing in the Indonesian stock market to identify a list of undervalued companies deemed suitable for investment. The analytical method used in this study is quantitative descriptive analysis. The research findings indicate that out of 178 companies listed on the Indonesian stock market, only 6 companies fall into the undervalued category with good financial performance based on the value investing approach and financial ratios. The 6 selected companies considered worthy for investment consideration are PT. Intanwijaya International Tbk. (INCI), PT. Wilmar Cahaya Indonesia Tbk. (CEKA), PT. Wismilak Inti Makmur Tbk (WIIM), PT Astra Otoparts Tbk (AUTO), PT Sekar Laut Tbk (SKLT), and PT Sat Nusapersada Tbk (PTSN).